“One is not Born, but Rather Becomes, a Woman”: Impressions of Women on the Career in Agribusiness and its Spaces - Heliani Berlato; Danilo Andretta; Thais Fernandes (BBR: Brazilian Business Review)
Studies on gender discrimination and women’s careers in organizations reinforce how much women are silenced in their speech, undermined in their skills, and paid less than men. However, there is little research on this topic in the context of agribusiness. In this sense, the objective of this study was to understand how gender discrimination is seen by women graduating from agricultural sciences programs. As a methodology, a questionnaire was applied and 315 respondents answered, and a Factor Analysis and, later, a Cluster Analysis were carried out. Five factors were identified, and, from that, two clusters were defined, called “maintainers of the patriarchal system” and “aware of protagonism”. Both clusters demarcate tensions about how women see discrimination and experience the multiple unfoldings of sexist behaviors and attitudes that permeate their career pathways in agribusiness.